STRATEGI GURU PENDIDIKAN AGAMA ISLAM DALAM PENGEMBANGAN NILAI-NILAI PENDIDIKAN MULTIKULTURAL DI SMK NEGERI 1 PALOPO - Irvan, Irvan; Takwim, Mardi; Yusuf, Munir (Institut Agama Islam Negeri (IAIN) Palopo, 2024)
The main problem of this thesis research is how to implement the values of multicultural education at SMK Negeri 1 Palopo. Then what is the PAI teacher's strategy in developing multicultural educational values, and what are the supporting and inhibiting factors in the process of developing multicultural educational values at SMK Negeri 1 Palopo. This thesis research uses descriptive qualitative research. The research location is at SMK Negeri 1 Palopo. With the method of observation, interviews, documentation. Data analysis by reducing data, presenting data, and verifying data. The findings in this study indicate that at SMK Negeri 1 Palopo it has implemented the values of multicultural education as there is education in Islam which includes tolerance values, peace values, tolerance values, justice values, honesty values, democratic values, religious values and togetherness values. The strategy for developing multicultural education values at SMK Negeri 1 Palopo uses several strategies including prayer methods, reading the Koran for each student, group work methods, discussion methods, and collaborative methods between parents and students. The results of the strategy for developing multicultural educational values in students are the growth of democratic attitudes, tolerance, justice, peace, honesty, religion, togetherness, the absence of conflicts due to differences in culture, race, ethnicity, social and religious status. School is a place of education that will print the nation's generation and determine the nation's destiny in the future by using appropriate learning methods. Education, especially religious education, is the main joint of knowledge in the application and development of multicultural education in order to shape students' personality attitudes. In the learning process, of course, it will not go according to the wishes of education, there must be supporting and inhibiting factors. The supporting factors experienced by PAI teachers in the process of developing multicultural educational values include a strategic and supportive school environment, teachers and school staff who are supportive and work well together, realize good curriculum and students accept learning methods well. As for the things that become obstacles, namely the lack of socialization regarding multiculturalism, the absence of pamphlets in magazines based on multicultural education, and the lack of student creativity about the importance of multicultural education